Is ITP really a desirable indication for teaching laparoscopic splenectomy? Cohort study. Issue 6 (2nd November 2019) - Radkowiak, Dorota; Wysocki, Michał; Zychowicz, Anna; Lasek, Anna; Major, Piotr; Pędziwiatr, Michał; Budzyński, Piotr; Zub-Pokrowiecka, Anna; Budzyński, Andrzej
Abstract: Background : We aimed to evaluate the outcomes of laparoscopic splenectomy (LS) in patients with immune thrombocytopenic purpura (ITP) compared with operated for other indications. Methods : Retrospective cohort study of patients who underwent LS in 1998–2017. Group 1 consisted of 256 patients operated for ITP, and Group 2 of 231 operated for other indications. Primary outcome was procedure difficulty. Secondary was perioperative course (30 days of surgery). Results : Patients in Group 1 were younger ( p < .001) with lower ASA ( p < .001). The spleen was larger in Group 2 ( p < .001). Operative time was longer in Group 2 [110 (80–150) vs. 90 (65–115) min; p < .001)]. Intraoperative blood loss was greater in Group 2 ( p < .001). Conversions were higher in Group 2 (4.76 vs. 6.93%, p = .037), as were intraoperative complications (7.79 vs. 3.91%, p = .048). Morbidity, reoperations and mortality did not differ between groups (respectively, p = .899, .697, and .999). Median length of stay was similar ( p = .211). Among the first 10 LSs performed by trainees, 63.66% were done for ITP. Later (after 11+ procedures) this dropped to 48.12% ( p = .002). Conclusions: ITP may be a preferred indication for surgeons training for LS. Patients' characteristics and intraoperative factors allow an expectation for a relatively easy and hassle-free operation in those patients.